2018
DOI: 10.1371/journal.pone.0207218
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolic events during warm autoimmune hemolytic anemia

Abstract: Thrombotic manifestations are a hallmark of many auto-immune diseases (AID), specially of warm autoimmune hemolytic anemia (wAIHA), as 15 to 33% of adults with wAIHA experience venous thromboembolic events (VTE). However, beyond the presence of positive antiphospholipid antibodies and splenectomy, risk factors for developing a VTE during wAIHA have not been clearly identified. The aim of this retrospective study was to characterize VTEs during wAIHA and to identify risk factors for VTE. Forty-eight patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 30 publications
5
67
4
2
Order By: Relevance
“…The risk of thrombosis in patients with AIHA, ITP, or ES was previously reported to be high in absolute terms, and compared to the risk in the general population . Our findings on the causes of death were ambiguous regarding cardiovascular‐related deaths, which included thromboembolic related deaths.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The risk of thrombosis in patients with AIHA, ITP, or ES was previously reported to be high in absolute terms, and compared to the risk in the general population . Our findings on the causes of death were ambiguous regarding cardiovascular‐related deaths, which included thromboembolic related deaths.…”
Section: Discussionmentioning
confidence: 62%
“…The incidence and prevalence of ES are unknown, although recent studies in children indicate that it may not be as rare as presumed . Although both AIHA and ITP were found to be associated with elevated risk of thrombosis and increased mortality, we know little about morbidity and mortality in patients with ES . Current knowledge regarding the prognosis and complications in adults with ES is based mostly on single‐case and small case series studies .…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the cross-talk between the complement system, inflammatory processes, and the coagulation cascade (100, 108, 109) might result in an increased frequency of thrombosis in CAD and CAS. Such a risk is definitely present in wAIHA (110,111). In CAD, this risk has been clearly documented in the most severely affected patients (73), and recent registry-based studies have found a slightly increased frequency of thrombosis in unselected CAD cohorts as well (112,113).…”
Section: Impact Of Caiha On Inflammationmentioning
confidence: 95%
“…In CAD, this risk has been clearly documented in the most severely affected patients (73), and recent registry-based studies have found a slightly increased frequency of thrombosis in unselected CAD cohorts as well (112,113). According to one AIHA study, leukocytes influenced the risk of thrombosis (111), and the tissue factor expression by granulocytes has been implicated as one of the links between inflammation and thrombosis (114). The role of this interaction is more unclear in CAD, however, due to the different immune pathogenesis and because CAD patients usually do not have elevated leukocyte counts (9).…”
Section: Impact Of Caiha On Inflammationmentioning
confidence: 99%
“…Transfusion should be treated with caution due to the risk of hemolytic transfusion reactions caused by alloantibodies of AIHA. Given the higher risk of thrombosis, long-term anticoagulation should be advised [8]. Despite the improved safety of Non-vitamin K antagonist oral anticoagulants (NOACs) compared with Vitamin K antagonists (VKAs) for extended anticoagulation of acute PE, treatment with NOACs is not without risk [9].…”
Section: Discussionmentioning
confidence: 99%